2005
DOI: 10.1063/1.1953873
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gate-leakage current on drain current collapse of unpassivated GaN∕AlGaN∕GaN high electron mobility transistors

Abstract: We report on a correlation between the gate leakage currents and the drain current collapse of GaN∕AlGaN∕GaN high electron mobility transistors. Unpassivated devices on intentionally undoped and doped (Si, 5×1018cm−3) heterostructures were investigated. We observed in the devices that the larger the gate leakage current, the smaller the drain current collapse measured at 50ns gate-voltage pulse turn on, and this correlation is independent of the doping of the structure. The correlation holds for two orders of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Traps in either the GaN buffer or AlGaN barrier layers also lead to the poor performance of device as they act as source for leakage current. Surface passivation by a suitable dielectric film is essential to mitigate the current collapse effect 1,2,6, 16 . Number of people have suggested that in SiN passivation Si incorporation at the AlGaN surface as shallow donor and helps in reducing surface traps and hence the current collapse.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traps in either the GaN buffer or AlGaN barrier layers also lead to the poor performance of device as they act as source for leakage current. Surface passivation by a suitable dielectric film is essential to mitigate the current collapse effect 1,2,6, 16 . Number of people have suggested that in SiN passivation Si incorporation at the AlGaN surface as shallow donor and helps in reducing surface traps and hence the current collapse.…”
Section: Resultsmentioning
confidence: 99%
“…These devices are known for better IV characteristics and record high output power at RF frequencies. However, GaN HEMTs suffer from current collapse and frequency dispersion mainly due to trapping of electron in the active channel region [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . The trapping effect is mainly due to defects, dislocations which might have incorporated during HEMT structure growth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in spite of the similarity in static R ds,on , dynamic R ds,on is increased about 2.47 times compared to static R ds,on in low Mg doping, but just increased 1.53 times in high Mg doping. This is closely related to the gate leakage currents ( I GS ) in turn‐on transients [6]. In GaN power devices, I GS give a positive effect to current collapse phenomenon.…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…This confirms a large number of short-time-constant traps are removed using bilayer LPCVD passivation. The suppressed current collapse is probably due to the first thin layer of Si-rich LPCVD SiNx, which provides leakage path eliminating the AlGaN surface trapping [11]. The RF performance of these devices was characterized from 0.45 to 50 GHz using network analyzer.…”
Section: B Pulsed IV Measurementmentioning
confidence: 99%